Lectotypifications in species of Chusquea (Poaceae, Bambusoideae, Bambuseae) from southern South America - Guerreiro, Carolina; Lizarazu, Mabel; Vega, Andrea (Phytotaxa, 2014)
Lectotypes of Chusquea phacellophora, C. tenella, C. uruguayensis and C. valdiviensis are herein designated on the basis of specimens deposited at Museo Nacional de Historia Natural (MVM), Museúm National d´Historie Naturelle (P) and Smithsonian Institution (US) herbaria.